(3cJGH GdMGUds - (3LGHQ Hf MjGf Hf YHO Gddg Gdchaj, CHh ehSi, J (B200 (3g` s
(3ChdgG (B:s
(3GdMeO ddg NGdbfG hUfY Gddg Ydi UahJg ai NdbI eMeO hGdg hSde SjOi LYaQ Hf eMeO UdhGJ Gddg Ydjg bGd (B: (3aeG GdMGUd GdBf HYO gPg GdcJH ai GdehGRjf h eG GdefaYI HgG abdJ GdefaYI Yde GdJQGcjH s
(3BNQgG (B:s
(3CeG CadGWhf aEfg jfSH HYV GdGTjGA Edi GdSjGSI hHYVgG Edi GdVQhQI aGcTa Yf Pdc jJVM dc GdMb EfTGA Gddg JYGdi Je cJGH GdMGUd s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdNGeS YTQs
(3HgG fXGe GdJYbjHIs
(3eUOQ GbJfGA GdCUd (B:s
(3ShQjG (B(9318) s
Keywords: (3GdadSaI hGdefWbs